Collection building trend among the institutes of higher learning in India: a preferential race between print and electronic resources. Issue 4 (3rd October 2016) - Pandita, Ramesh; Singh, Shivendra
Abstract : Purpose: The present study aims to assess the resource procurement preferences among the leading academic libraries of the institutes of higher learning across India. The study analyses the amount and percentage of budget spent by the institutions under study during the period 2012-2013, 2013-2014 and 2014-2015 on the procurement of print and electronic resources in their libraries. The study also discusses about concerns with regard to the subscription of e-resources and the reasons for weaning interest among the Indian academicians towards the print resources. Design/methodology/approach: By and large, the scope of the study is limited to institutes of higher learning across India, but reflects a great deal of relevance to the global higher education practices. The study has been undertaken on the 20 leading institutes each from Universities, Institutes of Management and Institutes of Technology in India, based on the ranking list released by the Ministry of Human Resource Development, Government of India, on 4 April 2016. Findings: The electronic documents are the dominant forms of present day library procurements in India, with the print struggling to retain its readership. The Institutes of Engineering and Technology and Management have almost similar procurement preferences, spending almost three-fourth of their library budgets on the procurement of e-documents. On average, the University libraries in India have spent 43.54 per cent of their budget on the procurement of print resources and 56.46 per cent of their budget on the procurement of electronic resources during the period of study. Similarly, on average, each Institute of Engineering and Technology has spent 24.04 per cent of their library budget on the procurement of print documents and 75.96 per cent towards the procurement of electronic resources, whereas 27.51 per cent of the library budget by the Institutes of Management in India is being spent on the procurement of print resources and 72.49 per cent towards the procurement of electronic resources. Originality/value: The study is original and is first of its kind, undertaken on three different category of institutions, based on the national ranking of the country.